A review of the status and biogeography of the lizard genera Celestus and Diploglossus (Squamata: Anguidae), with description of two new species from Costa Rica - Savage, Jay M (Universidad de Costa Rica, 1993)
Sé describe dos especies nuevas de l8gartijas diploglosinas. Celeitus hylaiús y Celestus orobius